Man’s Pursuit of Meaning: Unexpected Termination Bolsters One’s Autonomous Motivation in an Irrelevant Ensuing Activity - Wei, Wei; Mo, Zan; Liu, Jianhua; Meng, Liang (Frontiers in Human Neuroscience, 2020)
Meaningfulness has been suggested as one of the fundamental psychological needs, as one would actively pursue meaning in both his/her work life and personal life. Previous studies consistently showed that a lack of meaning in work would reduce one’s autonomous motivation in the current job, which is the motivation to engage in self-determined activities driven by one’s own interests or personal beliefs. However, researchers overlooked the fact that in work settings, it is not uncommon that people work on multiple tasks in a row. As a result, the cross-task effect of work meaningfulness remains understudied. Based on the meaning maintenance model (MMM) and the suggested fluid compensation strategy, we predicted that the disappearance of the meaning of work may induce a compensatory response and thus enhance one’s autonomous motivation in an irrelevant ensuing activity. To test this hypothesis, we invited participants to work on an encyclopedic knowledge quiz in Session 1 and a StopWatch (SW) task in Session 2. A between-subject design was adopted. While participants in the control group successfully completed their tasks in Session 1, those in the experimental group encountered unexpected program quits by the end of the quiz, and their previous efforts suddenly became futile and meaningless. Electroencephalography was recorded during the experiment to measure reward positivity (RewP). In Session 2, a more pronounced RewP in the win–lose difference wave was observed in the experimental group in contrast to the control group, suggesting that the disappearance of the meaning of work enhanced one’s autonomous motivation in an irrelevant activity that follows. Therefore, results of this study provided preliminary electrophysiological evidence for one’s pursuit of meaning and the compensation effect induced by the disappearance of the meaning of work.